2022
DOI: 10.3390/genes13122306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Acetylcysteine on the Proliferation, Hormone Secretion Level, and Gene Expression Profiles of Goat Ovarian Granulosa Cells

Abstract: The purpose of this paper was to investigate the effects of N-acetylcysteine (NAC) on the proliferation, hormone secretion, and mRNA expression profiles of ovarian granulosa cells (GCs) in vitro. A total of 12 ovaries from 6 follicular-stage goats were collected for granulosa cell extraction. The optimum concentration of NAC addition was determined to be 200 μM via the Cell Counting Kit 8 (CCK-8) method. Next, GCs were cultured in a medium supplemented with 200 μM NAC (200 μM NAC group) and 0 μ M NAC (control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A minor increase in intracellular ROS levels may induce cell proliferation by activating signaling cascades [23]. Antioxidants also increase cell proliferation by reducing intracellular ROS levels [24, 25]. Thus, we questioned whether the increased proliferation by 60 Hz ELF-EMF was triggered by changes in intracellular and/or mitochondrial ROS levels.…”
Section: Resultsmentioning
confidence: 99%
“…A minor increase in intracellular ROS levels may induce cell proliferation by activating signaling cascades [23]. Antioxidants also increase cell proliferation by reducing intracellular ROS levels [24, 25]. Thus, we questioned whether the increased proliferation by 60 Hz ELF-EMF was triggered by changes in intracellular and/or mitochondrial ROS levels.…”
Section: Resultsmentioning
confidence: 99%
“…Among these pathways, neuroactive ligand-receptor interactions were enriched in the highest number of DEGs and showed the most significant differences, followed by the calcium signalling pathway and the cAMP signalling pathway. Studies have shown that interactions between neuroactive ligands and receptors are involved in granulosa cell proliferation [43], and these interactions, along with signalling pathways such as the PPAR and cAMP signalling pathways, are important for ovarian development [44] and are related to the occurrence and development of PCOS [45,46]. The calcium signalling pathway is crucial in regulating various cellular processes such as cell growth, differentiation, proliferation, apoptosis, and other cellular processes [47].…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro experiments, the addition of 1.5 mM of NAC to oocyte maturation medium has been shown to increase the proportion of embryos reaching the blastocyst stage [18]. Moreover, 200 µM of NAC could activate the cAMP and Wnt signaling pathways to significantly enhance proliferation and hormonal secretion by goat ovarian GCs, with the process being essential for improving follicular growth and reproductive performance in ewes [19]. Dietary supplementation of 0.07% NAC has further been found to regulate endometrial immune and inflammatory responses through the PI3K/Akt and PPAR pathways, hence improving the survival rate of goat embryos in early pregnancy [20].…”
Section: Introductionmentioning
confidence: 99%